TRAINING OF TRANSLATORS AND A NEW APPROACH TO TRANSLATION IN THE DEVELOPMENT OF NATIONAL EDUCATION - Baxodirovich, Tursunov Bexzodbek (Journal of Higher Education and Academic Advancement, 2025)
Objective: This study examines the state of translation practices during the years of independence, highlighting both progress and challenges. While practical translation experienced a revival, theoretical research and studies on translation directions and perspectives saw a decline. Methods: The research is based on an analysis of translation practices, educational improvements, and the development of professional training in higher education institutions. It evaluates both qualitative and quantitative aspects of translation studies and their impact on the field. Results: Findings indicate that despite the weakening of theoretical studies, translation teaching and professional training have improved. Additionally, the study identifies current achievements and shortcomings in translation practices, providing insights into their development. Novelty: This study offers a unique perspective on the simultaneous progress and decline within the field of translation. It highlights the paradox of increased practical application alongside reduced theoretical exploration, emphasizing the need for a balanced approach to translation studies.